Soil organic matter quality exerts a stronger control than stoichiometry on microbial substrate use efficiency along a latitudinal transect. (June 2018) - Takriti, Mounir; Wild, Birgit; Schnecker, Jörg; Mooshammer, Maria; Knoltsch, Anna; Lashchinskiy, Nikolay; Eloy Alves, Ricardo J.; Gentsch, Norman; Gittel, Antje; Mikutta, Robert; Wanek, Wolfgang; Richter, Andreas
Abstract: A substantial portion of soil organic matter (SOM) is of microbial origin. The efficiency with which soil microorganisms can convert their substrate carbon (C) into biomass, compared to how much is lost as respiration, thus co-determines the carbon storage potential of soils. Despite increasing insight into soil microbial C cycling, empirical measurements of microbial C processing across biomes and across soil horizons remain sparse. The theory of ecological stoichiometry predicts that microbial carbon use efficiency (CUE), i.e. growth over uptake of organic C, strongly depends on the relative availability of C and nutrients, particularly N, as microorganisms will either respire excess C or conserve C while mineralising excess nutrients. Microbial CUE is thus expected to increase from high to low latitudes and from topsoil to subsoil as the soil C:N and the stoichiometric imbalance between SOM and the microbial biomass decrease. To test these hypotheses, we collected soil samples from the organic topsoil, mineral topsoil, and mineral subsoil of seven sites along a 1500-km latitudinal transect in Western Siberia. As a proxy for CUE, we measured the microbial substrate use efficiency (SUE) of added substrates by incubating soil samples with a mixture of 13 C labelled sugars, amino sugars, amino acids, and organic acids and tracing 13 C into microbial biomass and released CO2 . In addition to soil and microbial C:N stoichiometry, we also determined the potential extracellular enzyme activities of cellobiohydrolase (CBH) and phenol oxidase (POX) and used the CBH:POX ratio as an indicator of SOM substrate quality. We found an overall decrease of SUE with latitude, corresponding to a decrease in mean annual temperature, in mineral soil horizons. SUE decreased with decreasing stoichiometric imbalance in the organic and mineral topsoil, while a relationship of SUE with soil C:N was only found in the mineral topsoil. However, contrary to our hypothesis, SUE did not increase with soil depth and mineral subsoils displayed lower average SUE than mineral topsoils. Both within individual horizons and across all horizons SUE was strongly correlated with CBH:POX ratio as well as with climate variables. Since enzyme activities likely reflect the chemical properties of SOM, our results indicate that SOM quality exerts a stronger control on SUE than SOM stoichiometry, particularly in subsoils were SOM has been turned over repeatedly and there is little variation in SOM elemental ratios. Highlights: We measured soil microbial substrate use efficiency along a latitudinal transect. No clear relationship between microbial SUE and soil stoichiometry was found. Extracellular enzyme activities and MAP were strongly correlated with SUE. SUE was lower in mineral subsoil than in mineral topsoil. We conclude that SOM quality exerts a stronger control on SUE than stoichiometry.